The Cultivation and Development of Regional Languages in the Era of Smart Society 5.0 - Ida Bagus Rai Putra; Gusti Nyoman Mastini; I Wayan Mandra; Gek Diah Desi Sentana; I Gede Bagus Wisnu Bayu Temaja (West Science Social and Humanities Studies, 2025)
This study aims to examine the strategies for cultivating and developing regional languages within the context of Smart Society 5.0; a society that places humans at the center of technological innovation. Regional languages are vital cultural assets that reflect local identity and values. However, amid the currents of globalization and the dominance of national and foreign languages in digital spaces, many regional languages are experiencing a decline in speakers, particularly among the younger generation. This research employs a descriptive qualitative approach through a literature review of journal articles, books, policy documents, and official reports. The findings indicate that regional language development through school-based local content, teacher training, and community involvement proves effective when supported by strong policies and the use of digital technology. Educational apps, online dictionaries, and multimedia content present significant opportunities to engage the interest of younger generations. The role of cultural communities, traditional institutions, and local governments is also crucial in revitalizing the function of regional languages in daily life. Therefore, preservation strategies must integrate cultural, educational, and technological approaches in a sustainable manner. This study recommends a community-based collaborative model and a digital ecosystem as adaptive preservation strategies for the challenges of the Smart Society 5.0 era.